EKSTRAKSI DAN KARAKTERISTIK MINYAK IKAN SEMBILANG (Paraplotosus albilabris) DENGAN BAHAN PELARUT YANG BEBEDA - Apri_Nur_Azman Apri_Nur_Azman; sumarto_sumarto sumarto_sumarto; Edison_Edison Edison_Edison (Fakultas Perikanan dan Kelautan, Universitas Riau, 2018)
This study aims to determine the characteristics of catfish (Paraplotosus albilabris) oil by using different solvent extraction agent. The method used in this study is experimental method using a Completely Randomized Design (CRD) as a treatment is a different type of solvent i.e. ethanol, ethyl acetate, and n-hexane. The result of fish oil extraction which obtained using ethanol, ethyl acetate, and n-hexane solvent produced different rendement levels i.e. 14.59%, 11.28%, and7.48%, respectively. The Acid value of catfish oil using ethanol solvent is 224.06 mg/g, ethyl acetate solvent 206.76 mg/g, andn-heksan solvent 106.83 mg/g. The Iodine value of catfish oil using ethanol solvent is 83.66 mg/ml, ethyl acetate solvent72.81 mg/ml, and n-hexane solvent 82.29 mg/ml. TheStraaponification value of catfish oil using ethanol solvent is334.58 mg/ml, ethyl acetate solvent is 333.70 mg/ml, and n- hexane solvent 303.17 mg/ml.